Correction: Synthesis of dibenzocycloketones by acyl radical cyclization from aromatic carboxylic acids using methylene blue as a photocatalyst. Issue 4 (6th February 2020) - Jiang, Hongshuo; Mao, Guijie; Wu, Hongfeng; An, Qi; Zuo, Minghui; Guo, Weihao; Xu, Chunzhao; Sun, Zhizhong; Chu, Wenyi
Abstract : Correction for 'Synthesis of dibenzocycloketones by acyl radical cyclization from aromatic carboxylic acids using methylene blue as a photocatalyst' by Hongshuo Jiang et al., Green Chem., 2019, 21, 5368–5373.